Cadmium induces DNA damage in tobacco roots, but no DNA damage, somatic mutations or homologous recombination in tobacco leaves - Gichner, Tomás; Patková, Zdenka; Száková, Jirina; Demnerová, Katerina (Mutation research, 2004)
The heavy metal cadmium (Cd(2+)) applied on tobacco roots in the form of cadmium chloride, induced significantly higher levels of DNA damage as measured by the cellular Comet assay than did treatment of isolated root nuclei, analyzed by use of the acellular Comet assay. DNA damage induced by Cd(2+) in roots of a transgenic catalase-deficient tobacco line (CAT1AS) was higher than in wild-type tobacco (SR1) roots. In contrast to treatment with the positive control ethyl methanesulphonate, Cd(2+) induced no significant DNA damage in leaf nuclei, and neither somatic mutations, nor homologous recombination as measured by the GUS genereactivation assay, were observed in leaves. Analysis of the accumulation of cadmium by inductively coupled plasma optical emission spectrometry demonstrates that roots accumulate almost 50-fold more cadmium than above-ground parts of the tobacco seedlings. This may explain the absence of Cd(2+) genotoxicity in leaves.
Keywords: kořeny rostlin; kometový test; poškození DNA; Nicotiana; Dose-Response Relationship, Drug; Mutation; listy rostlin; Cadmium; spektrální analýza; kadmium; vztah mezi dávkou a účinkem léčiva; DNA Damage; Plant Roots; tabák; Plant Leaves; rekombinace genetická; Spectrum Analysis; Comet Assay; Recombination, Genetic; mutace